Produção de hidrogênio em reator anaeróbio de leito fixo e fluxo ascendente a partir de efluente de fecularia - Torres, Douglas Guedes Batista (2014)
Hydrogen is naturally formed in intermediate stages of anaerobic digestion and is subsequently consumed to generate products such as methane and hydrogen sulphide. So, in order to increase the energetic efficiency of gases produced in the system, it was necessary to separate hydrogen. It is essential to interrupt hydrogen consumption by methanogenic and sulphidegenic phases of anaerobic digestion process. As the effluent from cassava processing presents high concentration of sugars, there may be some possibility to favor the acidogenic digestion process, which provides better conditions to produce hydrogen gas and inhibit methanogenic archaea. Thus, this trial aims at evaluating hydrogen production from anaerobic digestion of wastewater from the cassava manufacturing process in an upflow anaerobic reactor, where bamboo was used as support medium. Four experimental runs (R1, R2, R3 and R4) were carried out in a 3.0 L plexiglass reactor, operated at 0.75 h-1 flow rate and Hydraulic Detention Time (HDT) of 4 hours. The assays were inoculated with 10% of the effective volume of an anaerobic sludge digester installed on a cassava industry at 95 °C for 15 min to eliminate microorganisms that produce methane. The cassava pH adjustment was managed to 6.0, but only at the R1 run. In R2, R3 and R4 runs, without any pH change, the values ranged from 3.74 to 4.47. The reactors showed a consumption average from total sugar superior at 80%, whose COD removals were 55.26, 15.27, 46.16 and 40.42% for R1, R2, R3 and R4, respectively. It was also observed that biogas flow decreasing provided greater biomass accumulation in the reactor. Thus, the results of HDT values were obtained by hydrodynamic essay of 3.75, 1.08, 1.83 and 2.43 for R1, R2 R3 and R4, respectively. It can also be observed that the process of hydrogen generation was associated with the metabolic route to generate butyric acid, since the increase of this product from acidogenesis resulted in higher amounts of hydrogen. It was also pointed out that the peak incidences of lactic and propionic acid concentrations in the effluent occurred simultaneously to the decreased production, which could indicate H2 consumption. The use of cassava without pH correction in R2, R3 and R4 resulted in lower productions of H2 maybe as a result of solventogenesis possibility that was recorded by the increase in butanol and ethanol production, which matched to the hydrogen flow reduction. The highest molar flow rates of H2 were observed in R1, with maximum value of 10.6mmolH2.h-1. R2 essay showed the highest percentages of hydrogen in biogas (45.37%) and maximum flow of 3.37 mmolH2.h-1, whose highest concentrations of calcium in cassava lots were used in that period. However, R3 and R4 reactors showed the highest flows (0.99 and 1.80 mmolH2.h-1). Thus, it should be highlighted the importance of correcting pH of cassava industry wastewater and monitoring alcohols and volatile fatty acids generated during this process.